Land use/land cover classification and change analysis by multitemporal remote sensing data - Nor Ashifah, Hamzah (2015)
Kuantan is a one largest district in Pahang. Kuantan have rapid development in every aspect. By using Multi-temporal satellite images and application of remote sensing and GIS for land use and land cover change detection were used. The main challenge in land use and land cover changes using the remote sensing data which how to provide the accurate and timely geospatial information. The production of thematic map from this classification by using an image classification is one of the most common way application of remote sensing. This research briefly reviews the background, methods of accuracy assessment that commonly used and recommended in the research literature.This research also for to access the accuracy of multi-temporal classification and change detection. Process that involve in this research are selection data satellite, data correction, classification process, accuracy assessmen